O ensino de matemática em uma perspectiva inclusiva : experiência com uma aluna com deficiência visual na construção e aplicação de um material didático para aulas de simetria - Rodrigues, Jorge de Menezes (2018)
The present work had as objective to analyze the signs of involvement and learning of a student with visual impairment from the construction and application of an adapted didactic material in symmetry classes. The research was developed with three participants, two mathematics teachers, one with low vision and the researcher professor, and one student with visual impairment. The research consisted of a case study guided by the methodological framework of the qualitative approach and the investigative process happened in two phases during the year 2017, in the city of Manaus. The first phase, called Exploratory, was carried out at the school of the participant student of the research and had the intention to verify the special educational needs of the student in mathematics classes so that we could start building, from the data produced, a didactic material adapted for the teaching of symmetry, with a view to promoting inclusive education. The second phase, which we named Construction and Application of Adapted Didactic Material, was carried out at the Specialized Educational Service where the student was enrolled in the year of the research, in this phase a didactic material was developed by the participants of the research and later applied with the student with visual impairment. For the production of data, we used as an instrument and research technic, the semi structured interview, structured observation, video recording and field diary; The results obtained in the research demonstrated that the construction and application of didactic material adapted for the teaching of symmetry, presented subsidies during the research process that enabled the student with visual impairment to grasp the concept of symmetry. In the application of the material, we highlight the interaction between the student and the researcher teacher, who provided the student with the search for systematization, abstraction and broad generalization of aspects involving symmetry. Thus, data analysis pointed out that the existence of a didactic material that meets the special educational needs of students with visual impairment contributes to the inclusion process in mathematics classes.